ANALISIS FUNGSI KEPEMIMPINAN ORGANISASI TERHADAP KINERJA PEGAWAI (Studi Badan Pelayanan Perizinan Terpadu Dan Penanaman Modal Kota Cimahi ) - Farid Riadi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
Organizational progress and decline depends on the leadership qualities of a leader. Viewed from the point of view of each leader always placed at one very important point. The role of the leader in an organization or group is very important. Because in that role, a leader will help the organization realize its vision and mission. The objectives of this study can be formulated as follows: To determine the Effect of Leadership Functions on Employee Performance of Badan Pelayanan Perizinan Terpadu Dan Penanaman Modal Kota Cimahi. This Research Method is descriptive quantitative research, which describes the relationship between variables by analyzing numerical data using statistical methods through hypothesis testing. In this study took the entire employee population in the Office of Badan Pelayanan Perizinan Terpadu Dan Penanaman Modal Kota Cimahi, which consists of 50 people. The results of simple correlation analysis show that the role of leadership function is positive and significant at 56.4%, meaning that the roles and functions of leadership are very well implemented in the Badan Pelayanan Perizinan Terpadu Dan Penanaman Modal Kota Cimahi, while employee performance is 52.9%; meaning that the development of performance is determined or influenced by leadership roles.